The coexistence of paroxysmal hemicrania and temporomandibular disorder: Importance of multidisciplinary approach - André Luís Porporatti (Indian Journal of Dental Research, 2014)
Paroxysmal hemicrania (PH) is a trigeminal autonomic cephalalgia, a rare primary headache characterized by unilateral periorbital and/or temporal attacks of severe intensity and short duration. In this situation, the determination of a correct diagnosis is crucial for the establishment of a proper management strategy. In the case of head and facial pain, this step is usually a big challenge since many conditions share the same features, as some primary headaches and temporomandibular disorders (TMD). The relationship between PH and TMD has not been determined. This paper describes a case of a female patient diagnosed with TMD and presenting concomitant headache attacks fulfilling the International Headache Society′s criteria for PH. It is also emphasized the importance of dentist in this scenario, for many times responsible for the initial diagnosis of facial/head pain. Moreover, it is presented an integrated and simultaneously approach of both conditions, PH and TMD.